Novel scheme for analysing the noise limitations of average and guided soliton communication systems - Zakaria, Zahariah (2013)
This thesis presents analytical and numerical investigations of optical soliton transmission in optical fibre communication systems. The basic principles of nonlinear pulse propagation in optical fibre are discussed followed by discussion of the main limitations for an amplified soliton based system. The goal of this work is to study in-depth the soliton propagation and to analyse the bit pattern noise analysis and multi-slot analysis of system performance. First, a performance comparison of mqocss, VPI and OptSim for single and WDM transmission systems is presented. The purpose of this comparison is to assess the degree of variability between independently written numerical simulation codes and the commercial software available in the market. Secondly, a study of average soliton systems with 35, 50 and 70 km amplifier spacing is presented both analytically and numerically. The effect of modifying the existing rule of thumb formulae is presented in terms of a design diagram. This is then compared to the numerical simulations. The introduction of optimum jitter parameter, αsq = 0.05 in the formulation of GH limitation and optimum ratio of Belec to Bopt, BRAT = 0.4, of the ASE limitation improve the better comparison between analytical and numerical results. A series of design diagram with Gordon-Haus (GH) jitter, signal to noise ratio (SNR) and soliton collapse limited transmission is also introduced. The same study has been repeated for guided soliton systems. Finally a significant portion of this work is devoted to the noise analysis of GH and SNR limited system transmission. A novel technique is introduced which is designed to distinguish between the effects of dispersion and jitter in analysing the limitations of system performance. These are represented in the form of probability distribution function on amplitude and timing jitter, by introducing the two methods (A and B), referring to the eye diagrams of the system limitations. Another technique analysis is presenting the energy plots of En+1 and En-1, the energy adjacent to bit under consideration. The plot also explains the limitation due to amplified soliton, ASL. Key words: Optical amplification, Guiding Centre Soliton, Guided Soliton, GH and SNR limited transmission, Noise analysis